MAIN DIRECTIONS OF USING INFORMATION TECHNOLOGY IN MODERN EDUCATIONAL SOCIETY (Ustozlar uchun, 2024)
Abstract: In the article, information technology’s directions which are used in educational society nowadays, increase in intellectual capabilities and progresses in this regard are analyzed.